UMPSA improves position in QS World University Rankings 2025 - Hazmin, Aris (UMPSA, 2024)
PEKAN, 5 June 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has successfully elevated its position in the Quacquarelli Symonds (QS) World University Rankings (WUR) 2025, securing a place in the 741-750 range globally, compared to 781-790 in 2024.